Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1002/hed.2880160307
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma of the jaw

Abstract: We found that tumor size and surgical margins were significant prognostic factors. Early diagnosis of these tumors is mandatory to improve survival; the role of Ct and Rt is still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
56
3
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 21 publications
11
56
3
1
Order By: Relevance
“…This is in accordance with some (Caron et al, 1971;Garrington et al, 1967) but not most of prior studies in which the occurrence of chondroplastic subtype was found most commonly (Clark et al, 1983;Delgado et al, 1994;Freyschmidt and Ostertag, 1988;Goepfert et al, 1990;Salvati et al, 1993;Vege et al, 1991). Huvos et al found the fibroblastic to be most common (Huvos,1991).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in accordance with some (Caron et al, 1971;Garrington et al, 1967) but not most of prior studies in which the occurrence of chondroplastic subtype was found most commonly (Clark et al, 1983;Delgado et al, 1994;Freyschmidt and Ostertag, 1988;Goepfert et al, 1990;Salvati et al, 1993;Vege et al, 1991). Huvos et al found the fibroblastic to be most common (Huvos,1991).…”
Section: Discussionsupporting
confidence: 89%
“…The present study had only two cases of metastasis in the lung (5%). In earlier studies it was assumed that osteosarcoma in the jaws have a lesser grade of differentiation than osteosarcoma of the long bones (Roca et al, 1970;Russ and Jesse, 1980) whereas recent studies report high-grade tumours in 87e90% of osteosarcoma of the jaws (Bertoni et al, 1991;Delgado et al, 1994). However, OSJ shows significantly less metastasis than osteosarcoma of the long bones (Clark et al, 1983;Delgado et al, 1994;Mark et al, 1991) with a preference to local relapse (Batsakis, 1984).…”
Section: Discussionmentioning
confidence: 93%
“…10 OS of long bones affects mainly adolescents and young adults, where as gnathic OS seen mainly in middle age (third to fourth decade of life). [11][12][13][14][15][16] However, the peculiarity in our sample was that OS is mostly seen in young adults (second decade). Similar age group was afftected in an Iranian study.…”
Section: Discussionmentioning
confidence: 95%
“…17,18 OS of jaws rarely metastasizes to other parts of the body as seen in the present patients where there was no metastasis. [11][12][13] With respect to treatment, controversy still exists regarding the combination of surgery, radiotherapy and chemotherapy. [19][20][21] However, in all 13 cases of OS, here were treated with a combination of surgery and radiotherapy.…”
Section: Original Articlementioning
confidence: 99%
“…Osteosarcomas of the head and neck represent a small percentage of osteosarcomas with studies reporting occurrences between 0.5-8.1% 1,[5][6][7][8][9][10][11][12] and an average between 6 -7%. Head and neck osteosarcomas are infrequent and usually present in the third to fourth decades of life, almost a decade after the most common presentation of long-bone tumors.…”
mentioning
confidence: 99%